(untitled) (American Journal of Islam and Society, 2006)
This paper is an attempt to understand “Muslims’ voices” at the advent of the twenty-first century, especially the angry tone within. I would argue that such anger could be construed by situating the voices in the context of “pure war” constituted by terrorism used by different groups in the name of Islam, as well as state violence used in the name of security and order at the expense of rights and democracy. When the state exercises more control over its population through modern technology, which renders private space almost obsolete, rumors are used to offset its powerful gaze. Rumors about violence in the context of pure war, in turn, engender among Muslims some kinds of negative group cohesion that is fertile ground for anger directed against “the others,” as evidenced in Southeast Asia and elsewhere ...